LNA Prototype at 54 MHz to 88 MHz Using Discrete Components - Prapto Nugroho; Ivan Muhammad Ihsan Izetbegovic; Wahyu Dewanto (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2020)
This paper presents a design and prototyping of a Low-Noise Amplifier (LNA) for Wireless Regional Area Network (WRAN) operating in TV broadcast bands between 54 MHz – 88 MHz. The LNA design was then implemented by using discrete components. Components values was obtained by utilized DC analysis according to specifications which follows the Institute of Electrical and Electronics Engineering (IEEE) 802.22 standard on WRAN technical specifications. Simulation with 88 MHz produced S11 = -5.72 dB, S12 = -41.57 dB, S21 = 15.07 dB, S22 = -4.76 dB, Noise Figure (NF) = 3.9 dB, Input Third Order Intercept Point (IIP3) = 2.21 dBm, and power consumption of 45.39 mW. Experiments results on 88 MHz showed S11 = -6.13 dB and S21 = 0.74 dB.